Penggunaan Metode Steam Untuk Menstimulasi Kreativitas Anak - Septiani Hapidah (Student Scientific Creativity Journal, 2024)
The use of learning methods using the STEAM method to develop student creativity. Also be the key to being in the future, so that it has the ability to participate in the next life. STEAM basically needs to be taught from an early age to children so that children can think creatively and critically and can solve problems. The goal is to stimulate children's creativity with the STEAM method. The method carried out in this research is a qualitative method. The subjects in this study were children aged 5 - 6 years with a total of 30 people. The results of children's research can respond to the stimulus given well, children are able to express their imagination into works, creating existing materials into works of aesthetic value.